2022
DOI: 10.21608/asejaiqjsae.2022.241158
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Wheat Productivity Under Different Levels of Tillage, Seeding Rate and Nitrogen Sources in An Arid Region

Abstract: A two year field experiment was conducted during the winter season of 2018/2019 and 2019/2020, to evaluate grain yield and some agronomic traits of the Egyptian local wheat cultivar (Shandaweel 1) under three tillage practices; conventional (CT), partial (PT) and zero tillage (ZT), three nitrogen fertilizer treatments (180 kg mineral N ha -1 (N1), 144 kg N ha -1 + humic acid (N2) and 108 kg N ha -1 + humic acid + halex (N3) as well as three seeding rates (95 (S1), 119 (S2) and 143 (S3) kg ha -1 ). Conservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Plant dry weight was recorded variable among maize genotypes Gaile (2008) and Islam et al, (2019). Also, maize plant dry weight increased with growth progression, but, the rate of increase of dry weight was highest at 60 to 90 days after sowing, the results presented here were in agreement with results of Shaalan et al, (2015), Koca and Erekul (2016) and Islam et al, (2019). With increasing plant density, plant dry weight decreased and our results for this trait were in harmony with those of Karashin (2014) who found that increasing plant density from102,040 to 142,850 plant per hectare, plant dry weight decreased from (0.212 to 0.168 kg plant -1 ).…”
Section: Plant Characterssupporting
confidence: 89%
See 2 more Smart Citations
“…Plant dry weight was recorded variable among maize genotypes Gaile (2008) and Islam et al, (2019). Also, maize plant dry weight increased with growth progression, but, the rate of increase of dry weight was highest at 60 to 90 days after sowing, the results presented here were in agreement with results of Shaalan et al, (2015), Koca and Erekul (2016) and Islam et al, (2019). With increasing plant density, plant dry weight decreased and our results for this trait were in harmony with those of Karashin (2014) who found that increasing plant density from102,040 to 142,850 plant per hectare, plant dry weight decreased from (0.212 to 0.168 kg plant -1 ).…”
Section: Plant Characterssupporting
confidence: 89%
“…Meanwhile, a progressive increase in total dry forage yield was obtained with progress of maize-plant development towards physiological maturity with variable rate depending on stage of growth Cusicanqui and Lauer (1999). Shaalan et al, (2015), found that, total dry forage yield, increased from 45 to 75 days after sowing (3.18 to 8.42 t. ha -1 , respectively). As plant population density increased, total dry forage yield increased Soto et al, (2002), Widdicomble and Thelen (2002), Turgut et al, (2005), Subedi et al, (2006), Stanton et al, (2007), Carpici et al, (2010, Baghdadi et al, (2012), Karashin (2014), Haddadi and Mohseni, (2016) and Opoku (2017).…”
Section: Yield and Qualitymentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding maize plant densities effect, the greater plant density of maize (100%) produced the highest grain and stover yields/fed in comparison with 75 and 50% of recommended density in both seasons. In this respect, many researchers reported that a reduction in maize grain yield/ha was obtained by intercropping maize with other crops such as millet El-salamouni, 2016 andSelim, 2018), fodder maize (Shaalan et al, 2015 andAmanullah andNivethitha, 2020), as well as a depression in stover yield/ha of maize was recorded by intercropping maize with fodder maize (Amanullah and Nivethitha, 2020) and cowpea (Chhetri and Sinha, 2020). Also, other researchers found that grain yield of maize /unit area was increased by increasing plant density of maize up to 100% when it was intercropped with groundnut (Ibrahim et al, 2019).…”
Section: -1 Grain Yield and Its Attributesmentioning
confidence: 99%